STUDI KASUS: KOHESI DAN KOHERENSI TAJUK RENCANA SURAT KABAR HARIAN KOMPAS “NOBEL PERDAMAIAN JUAN MANUEL SANTOS” - Siti Jamzaroh (Balai Bahasa Sulawesi Tengah, 2016)
This study is conducted to aim the description of cohesion and coherence which are transformed into (1)application of grammatical cohesion device, and (2) application of lexical cohesion. The research methods include (1) the stages of data provision, (2) the stages of data analysis, (3) the stage of data analysis presentation, The data provision is conducted by listening method and noting technique. The listening and noting results arethen classified by type of the cohesion. Analysis of the data by the distributional method with basic technique,that is divided element direct techniques, and advanced technique that is paraphrase. Presentation of the resultsis conducted by using informal methods. The results are 1) the grammatical cohesion are: a) reference: I, she/he, it, that, this; b) the conjunction of opposition, addition, causation, and period; b) substitution: nominal andclauses substitution; c) ellipsis: nominal ellipsis; and there is no lexical cohesion in the result.